2005
DOI: 10.1213/01.ane.0000139355.86522.d1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Meperidine on Thermoregulation in Mice: Involvement of ??2-Adrenoceptors

Abstract: Meperidine has potent antishivering properties. The underlying mechanisms are not fully elucidated, but recent investigations suggest that alpha2-adrenoceptors are likely to be involved. We performed the current study to investigate the effects of meperidine on nonshivering thermogenesis in a model of thermoregulation in mice. After injection (0.1 mL/kg intraperitoneally) of saline, meperidine (20 mg/kg), the specific alpha2-adrenoceptor antagonist atipamezole (2 mg/kg), plus saline or atipamezole plus meperid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
1
7
0
2
Order By: Relevance
“…Stimulation of a 2B -adrenoceptors in vascular smooth muscle leads to vasoconstriction, which causes the initial hypertension after the administration of a 2 -adrenoceptor agonists [23], and counteracts the hypotensive effects of a 2 -adrenoceptor agonists mediated via the a 2A -subtype. In addition, the a 2B -adrenoceptor seems to be required for the development of salt-induced hypertension [24], and is involved in mediation of the antinociceptive action of nitrous oxide [25,26,27 ] as well as in central thermoregulation [28,29]. The a 2C -adrenoceptor subtype has been demonstrated to modulate dopaminergic neurotransmission, various behavioural responses and to induce hypothermia [30,31].…”
Section: Pharmacologymentioning
confidence: 99%
See 1 more Smart Citation
“…Stimulation of a 2B -adrenoceptors in vascular smooth muscle leads to vasoconstriction, which causes the initial hypertension after the administration of a 2 -adrenoceptor agonists [23], and counteracts the hypotensive effects of a 2 -adrenoceptor agonists mediated via the a 2A -subtype. In addition, the a 2B -adrenoceptor seems to be required for the development of salt-induced hypertension [24], and is involved in mediation of the antinociceptive action of nitrous oxide [25,26,27 ] as well as in central thermoregulation [28,29]. The a 2C -adrenoceptor subtype has been demonstrated to modulate dopaminergic neurotransmission, various behavioural responses and to induce hypothermia [30,31].…”
Section: Pharmacologymentioning
confidence: 99%
“…This effect of etomidate may contribute to the cardiovascular stability of patients after the induction of anaesthesia with etomidate [34]. The opioid meperidine was shown to be a potent agonist at a 2 -adrenoceptors, and it has been suggested that some actions, especially the antishivering properties, are mediated by this mechanism [28,29].…”
Section: Pharmacologymentioning
confidence: 99%
“…According to our present results, this effect was abolished by administration of the ␣ 2 -adrenoceptor antagonist atipamezole, indicating an involvement of ␣ 2 -adrenoceptors in the mediation of meperidine actions. 10 This conclusion is supported by the fact that meperidine acts as an agonist at ␣ 2 -adrenoceptors in vitro in clinically relevant concentrations, showing highest affinity to the ␣ 2B -adrenoceptor subtype (␣ 2B , 8.6 Ϯ 0.3 M; ␣ 2C , 13.6 Ϯ 1.5 M; ␣ 2A , 38.6 Ϯ 0.7 M).…”
Section: Discussionmentioning
confidence: 90%
“…Because rodents try to resist hypothermia by nonshivering thermogenesis, we focused on a mouse model of nonshivering thermogenesis that has been used by our group before. 10 These experiments have revealed that meperidine mediates thermoregulatory effects via ␣ 2 -adrenoceptors but did not investigate any ␣ 2 -adrenoceptor subtype specifically. To evaluate the individual role of each of the three ␣ 2 -adrenoceptor subtypes, we compared impact of meperidine using wild-type mice and mice with deletion of the ␣ 2A -, ␣ 2B -, or ␣ 2C -adrenoceptor (knock-out mice).…”
mentioning
confidence: 99%
“…Zusammen mit der Beobachtung, dass sich die Wirkung von Pethidin auch durch hohe Dosen Naloxon nur unvollständig unterdrücken lässt [31], legt dies einen Wirkmechanismus unabhän-gig von Opioidrezeptoren nahe. Neuere experimentelle Daten deuten darauf hin, dass die Wirkung vielmehr auf einer agonistischen Wirkung von Pethidin am α 2 -Adrenozeptor beruhen könnte [38]. Die Applikation von Pethidin und dem potenten α 2 -Agonisten Clonidin könnten also 2 Variationen desselben pharmakologischen Prinzips sein.…”
Section: Introductionunclassified